Optimizing the Production from a Multizone Well by Selecting Appropriate Completion for a Well of Tal Block Pakistan - Arisar, M. R.; Hingoro, M. Z.; Abro, F. N.; Nawab, S.; Hullio, I. A. (Engineering, Technology & Applied Science Research, 2019)
Well completion is the process of construction a well geared up for production or injection. This mainly involves preparing the bottom of the hole to the required conditions, running the production tubing and associated downhole tools. Production from a multizone well can be obtained from a single tubing string as well as from dual tubing strings but it depends on pressure difference, depth and fluid present in the formation. This paper is based on the optimum well completions design for a multizone well of the Tal block region which contains four reservoirs of different formations: Lockhart (limestone), Hangu and Lumshiwal (sandstone), Samanasuk (limestone) & Datta (sandstone) having pressures of 7432psia, 7563psia, 7843psia, and 7982psia respectively. The well is producing four zones (multilayer well) and the generated numerical model for each completion (single string multizone completion and dual string multizone completion) shows better performance and economic feasibility.